Investing Information Technology and its Interactional Role in the Relationship between Value Added Intellectual Capital and Financial Performance An Analytical Comparative Rese - اسماعيل مصطفى منير; صالح حنين خالد (Journal of Economics and Administrative Sciences, 2016)
Abstract The basic aim of this research is to study the interactional effect of investing information technology on the relationship between value added intellectual capital and financial performance as literature review suggested on the theoretical level, including previous studies, with the deduction of its trends strongly predicted by research hypotheses and their content associated with the investment in intellectual capital after information technology tools being employed in this direction to improve the financial performance of the studied companies at the levels of both industrial and service sectors, a non-random sample was chosen included (40) forty Iraqi Joint-Stock companies traded at Iraq Stock Exchange distributed evenly between industrial and service sectors with a research horizon of (3) years (2011-2013). Then, variables are measured and analyzed on the financial and statistical levels, descriptively and explanatory, using panel data analysis technique to examine the spatial variation (between) and temporal one (years) . The measures of central tendency and dispersion, correlation and regression have also been used for statistical description and interpretation. Furthermore, after analysis of quantitative data of the sample companies were examined, and research hypotheses were tested on the two subsamples levels, it has reached to a number of conclusions confirm the validity of research hypotheses on the enhancement of investment in IT the relationship between value added intellectual capital and financial performance with positive trends as to banking sector; not the industrial one. Many recommendations have proposed the necessity of investment in intellectual capital which is expected to improve the efficient use of the organization’s resources and adding value to it and to achieve an adequate return for the competitive positions in the market. Future works have also indicated focusing on other research designs in the way of scientific investigation and theory improvement.